Asuhan Kebidanan Komprehensif Pada Ny.R Umur 23 Tahun G1P0A0 Dengan Kekurangan Energi Kronik (KEK) - Kisty Syakilatih Fauzah; Endang Susilowati; Mupliha Mupliha (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Maternal mortality remains a challenge in Indonesia, and one contributing factor is chronic malnutrition (CED), which impacts pregnancy, childbirth, the postpartum period, and the newborn. The 2022 registration report shows that of the 3,249,203 pregnant women whose MUAC was measured, 283,833 had a MUAC of less than 23.5 cm (at risk of CED), meaning 8.7% of these pregnant women were at risk of CED. In the Brebes area, the 2022 report recorded 3,475 pregnant women with CED. At the Bantarkawung Community Health Center in 2023, there were 36 cases of preeclampsia, 22 cases of transverse lie, 107 cases of CED, and anemia. Objective: Provide comprehensive midwifery care in accordance with standards of care for pregnant women, women giving birth, newborns, postpartum women, and family planning. Research method: Qualitative descriptive method, the type of research approach used in this study is a comprehensive case study approach. Results: Comprehensive care was provided to Mrs. R who suffered from chronic energy deficiency, and was successfully overcome. Delivery was carried out by caesarean section, the baby was born normally, and the postpartum period went smoothly, and the mother chose a contraceptive method, namely a three-monthly birth control injection. Conclusion: Comprehensive obstetric care has been proven effective in overcoming chronic energy deficiency, ensuring a safe delivery, a normal baby born, a normal postpartum period, and compliance with contraceptive methods.